Conference Review: The ICOM Museum Convention in Prague, August 2022 - Roeland Paardekooper (EXARC Journal, 2022)
The International Council of Museums, ICOM, has a habit of meeting every three years in a large General Conference. The last time was in Kyoto, Japan, in 2019. EXARC was present there, and we witnessed a heavy debate on the museum definition, but also spoke with many museum professionals from Japan and abroad. We worked in close cooperation with ICOM Netherlands that time, as we did three years earlier in Milan.